Electromuscular Incapacitating Devices Discharge and Risk of Severe Bradycardia. (June 2015) - Havranek, Stepan; Neuzil, Petr; Linhart, Ales
Abstract : Abstract: Electromuscular incapacitating devices (EMDs) are high-voltage, low-current stimulators causing involuntary muscle contractions and sensory response. Existing evidence about cardiac effects of EMD remains inconclusive. The aim of our study was to analyze electrocardiographic, echocardiographic, and microvolt T-wave alternans (MTWA) changes induced by EMD discharge. We examined 26 volunteers (22 men; median age 30 years) who underwent single standard 5-second duration exposure to TASER X26 under continuous echocardiographic and electrocardiographic monitoring. Microvolt T-wave alternans testing was performed at baseline (MTWA-1), as well as immediately and 60 minutes after EMD exposure (MTWA-2 and MTWA-3, respectively). Mean heart rate (HR) increased significantly from 88 ± 17 beats per minute before to 129 ± 17 beats per minute after exposure ( P < 0.001). However, in 2 individuals, an abrupt decrease in HR was observed. In one of them, interval between two consecutive beats increased up to 1.7 seconds during the discharge. New onset of supraventricular premature beats was observed after discharge in 1 patient. Results of MTWA-1, MTWA-2, and MTWA-3 tests were positive in one of the subjects, each time in a different case. Standard EMD exposure can be associated with a nonuniform reaction of HR and followed by heart rhythm disturbances. New MTWA positivity can reflect either the effect of EMD exposure or a potential false positivity of MTWA assessments.